Mark Twain’s compound complexity: Enhancing narrative in “The Adventures of Tom Sawyer” - Afna, Mauloeddin (Accentia: Journal of English Language and Education, 2024)
This study investigated the function and stylistic impact of compound words in Mark Twain's the Adventures of Tom Sawyer. Employing a mixed-methods approach combining corpus linguistics and qualitative content analysis, the study examined the types, frequency, and narrative contributions of compound words within the novel. Analysis revealed 127 unique compound words, with a preponderance of Noun + Noun constructions among compound nouns. These constructions facilitated concise meaning conveyance, contributing to the clarity and directness of Twain's prose. The study elucidated how Twain strategically employs compound words to enhance character development, enrich imagery, reflect regional dialect and culture, and subtly reinforce thematic elements. The varied use of compound types—open, closed, and hyphenated—contributes to a dynamic and engaging narrative style. This study underscored the importance of attending to micro-level linguistic features in literary analysis, demonstrating how seemingly simple lexical choices can significantly impact narrative construction and aesthetic effect. The findings offer valuable insights for linguists, literary scholars, and TESOL educators, enriching our understanding of Twain's enduring legacy as a master of language and storytelling.